Cytoplasmic Ca2+ influx mediates iron- and reactive oxygen species-dependent ferroptotic cell death in rice immunity - Wang, Juan; Choi, Won-Gyu; Nguyen, Nam Khoa; Liu, Dongping; Kim, Su-Hwa; Lim, Dongyeol; Hwang, Byung Kook; Jwa, Nam-Soo (Frontiers in Plant Science, 2024)
Iron- and reactive oxygen species (ROS)-dependent ferroptosis occurs in plant cells. Ca2+ acts as a conserved key mediator to control plant immune responses. Here, we report a novel role of cytoplasmic Ca2+ influx regulating ferroptotic cell death in rice immunity using pharmacological approaches. High Ca2+ influx triggered iron-dependent ROS accumulation, lipid peroxidation, and subsequent hypersensitive response (HR) cell death in rice (Oryza sativa). During Magnaporthe oryzae infection, 14 different Ca2+ influx regulators altered Ca2+, ROS and Fe2+ accumulation, glutathione reductase (GR) expression, glutathione (GSH) depletion and lipid peroxidation, leading to ferroptotic cell death in rice. High Ca2+ levels inhibited the reduction of glutathione isulphide (GSSG) to GSH in vitro. Ca2+ chelation by ethylene glycol-bis (2-aminoethylether)-N, N, N’, N’-tetra-acetic acid (EGTA) suppressed apoplastic Ca2+ influx in rice leaf sheaths during infection. Blocking apoplastic Ca2+ influx into the cytoplasm by Ca2+ chelation effectively suppressed Ca2+-mediated iron-dependent ROS accumulation and ferroptotic cell death. By contrast, acibenzolar-S-methyl (ASM), a plant defense activator, significantly enhanced Ca2+ influx, as well as ROS and iron accumulation to trigger ferroptotic cell death in rice. The cytoplasmic Ca2+ influx through calcium-permeable cation channels, including the putative resistosomes, could mediate iron- and ROS-dependent ferroptotic cell death under reduced GR expression levels in rice immune responses.